Tolerogenic Immunomodulation by PEGylated Antigenic Peptides - Pfeil, Jennifer; Simonetti, Mario; Lauer, Uta; Volkmer, Rudolf; von Thülen, Bianca; Durek, Pawel; Krähmer, Ralf; Leenders, Frank; Hamann, Alf; Hoffmann, Ute (Frontiers in Immunology, 2020)
Current treatments for autoimmune disorders rely on non-specific immunomodulatory as well as global immunosuppressive drugs, which show a variable degree of efficiency and are often accompanied by side effects. In contrast, strategies aiming at inducing antigen-specific tolerance promise an exclusive specificity of the immunomodulation. However, although successful in experimental models, peptide-based tolerogenic "inverse" vaccines have largely failed to show efficacy in clinical trials. Recent studies showed that repetitive T cell epitopes, coupling of peptides to autologous cells, or peptides coupled to nanoparticles can improve the tolerogenic efficacy of peptides, suggesting that size and biophysical properties of antigen constructs affect the induction of tolerance. As these materials bear hurdles with respect to preparation or regulatory aspects, we wondered whether conjugation of peptides to the well-established and clinically proven synthetic material polyethylene glycol (PEG) might also work. We here coupled the T cell epitope OVA323-339 to polyethylene glycols of different size and structure and tested the impact of these nano-sized constructs on regulatory (Treg) and effector T cells in the DO11.10 adoptive transfer mouse model. Systemic vaccination with PEGylated peptides resulted in highly increased frequencies of Foxp3+ Tregs as well as reduced frequencies of antigen-specific T cells producing pro-inflammatory TNF, compared to vaccination with the native peptide. PEGylation was found to extend the bioavailability of the model peptide. Both tolerogenicity and bioavailability were dependent on PEG size and structure. In conclusion, PEGylation of antigenic peptides is an effective and feasible strategy to improve Treg-inducing, peptide-based vaccines with potential use for the treatment of autoimmune diseases, allergies and transplant rejection.